Mercury and Other Biomedical Waste Management Practices among Dental Practitioners in India. (4th August 2014) - Singh, Raghuwar D.; Jurel, Sunit K.; Tripathi, Shuchi; Agrawal, Kaushal K.; Kumari, Reema
Abstract : Objectives . The objective of the study was to assess the awareness and performance towards dental waste including mercury management policy and practices among the dental practitioners in North India. Materials and Methods . An epidemiologic survey was conducted among 200 private dental practitioners. The survey form was composed of 29 self-administered questions frame based on knowledge, attitude, and those regarding the practices of dentists in relation to dental health-care waste management. The resulting data were coded and a statistical analysis was done. Results and Discussion . About 63.7% of the dentists were not aware of the different categories of biomedical waste generated in their clinics. Only 31.9% of the dentists correctly said that outdated and contaminated drugs come under cytotoxic waste. 46.2% said they break the needle and dispose of it and only 21.9% use needle burner to destroy it. 45.0% of the dentists dispose of the developer and fixer solutions by letting them into the sewer, 49.4% of them dilute the solutions and let them into sewer and only 5.6% return them to the supplier. About 40.6% of the dentists dispose of excess silver amalgam by throwing it into common bin. Conclusion . It was concluded that not all dentists were aware of the risks they were exposed to and only half of them observe infection control practices.